A review: Synthesis, modification and photocatalytic applications of ZnIn2S4. (10th July 2021) - Wang, Jie; Sun, Sijia; Zhou, Run; Li, Yangzi; He, Zetian; Ding, Hao; Chen, Daimei; Ao, Weihua
Graphical abstract: Highlights: ZnIn2 S4 based photocatalytic system can help solve the energy crisis and environmental problems. ZnIn2 S4 is easy to be synthesized and can be as stepping-stone for ternary metal sulfides. Developing interfaces of heterogeneous substances to enhance the inner driven force of charge transfer is suggested. The current progress in advanced photocatalytic applications is presented. Abstract: Solar energy is an ideal energy source for solving energy shortages and serious environmental problems. In the past few decades, photocatalytic technology which uses solar energy to deal with the above problems has caused great interest. ZnIn2 S4, as a layered ternary metal chalcogenide compound, has a series of advantages such as the wide light absorption range and adjustable bandgap. It has been applied in the different fields of photocatalysis in recent years. This review introduced the crystal structures and growth mechanism of ZnIn2 S4 and summarized the preparation methods of ZnIn2 S4 . Also, the promoted strategies of ZnIn2 S4 based photocatalytic system and their applications in the pollutant removal, hydrogen evolution, reduction of CO2, nitrogen fixation, and chemical synthesis was summarized. Furthermore, the challenges and development directions of the current ZnIn2 S4 based photocatalytic system were proposed. It is hoped that this review will help researchers design a better ZnIn2 S4 based photocatalytic system.